Personalised Nutritional Plan and Resistance Exercise Program to Improve Health Parameters in Celiac Women - Alejandro Martínez-Rodríguez; Daniela Alejandra Loaiza-Martínez; Javier Sánchez-Sánchez; Jacobo Á. Rubio-Arias; Fernando Alacid; Soledad Prats-Moya; María Martínez-Olcina; Rodrigo Yáñez-Sepúlveda; Pablo J. Marcos-Pardo (Foods, 2022)
Celiac disease (CD) is a permanent immune reaction to gluten in those with a genetic predisposition. This study was designed to evaluate menopause-associated symptoms, mood, bone quality, and IgA antibody levels in women with CD, untreated and treated with a gluten-free diet (GFD), and with or without resistance exercise. The randomised controlled trial was conducted on 28 Spanish women (>40 years old). Participants were divided into the following intervention groups: personalised gluten-free nutrition plan + exercise (GFD + E); personalised gluten-free nutrition plan (GFD); celiac controls (NO-GFD); and non-celiac controls (CONTROL). The participants responded to the Menopause Rating Scale and the Profile of Mood States (POMS) questionnaires. Bone quality was measured with ultrasound and IgA with a blood test. After 12 weeks of intervention, the GFD + E group showed significant improvement in urogenital symptoms and scored higher on the ‘vigour’ subscale of the POMS. Negative associations were found between the total score on the Menopause Rating Scale and the ‘vigour’ subscale of the POMS questionnaire. Only those women who underwent a personalised GFD nutritional intervention combined with resistance exercise demonstrated significant changes after the intervention.